A pilot study for determination of anxiety related SLC6A4 promoter S and L alleles in healthy Turkish athletes - ULUCAN, KORKUT (C M B ASSOC, 2017)
We aimed to analyze the allelic distribution of solute carrier family-6 member-4 promoter region in Turkish athletes. Recent studies showed the association of lesser expressing S allele with anxiety. Genotype percentages for LL, LS and SS genotypes were found as 46, 35 and 19, respectively. 38% of the males had LL, %38 had LS and 24% had SS genotypes. Percentages of LL, LS and SS genotypes were 54, 31 and 15 in females, respectively. 15 (58%) male and 18 (69%) females had L, 11 (42%) male and 8 (31%) females had S alleles. Variations in the association of the SLC6A4 alleles with neuropsychiatric disorders according to different nationalities have been reported. This is the first report showing that LL genotype and L allele in Turkish athletes was more frequent than SS genotype and S allele.
Keywords: Anxiety; Polymorphism; Serotonin transporter; Sports; Sport psychology; SEROTONIN TRANSPORTER GENE; EXTRACELLULAR 5-HT; 5-HIAA LEVELS; EXERCISE; POLYMORPHISMS; ASSOCIATION; IMPULSIVITY; PERFORMANCE; AGGRESSION; METABOLISM